Bright and photostable cyanine-styryl chromophores with green and red fluorescence colour for DNA staining. (8th September 2015) - Bohländer, Peggy R; Wagenknecht, Hans-Achim
Abstract: The synthesis and optical characterisation of a series of green- and red-emitting cyanine and cyanine-styryl dyes is presented that were developed based on the cyanine-indole-quinolinium and based on the thiazole red type structure. For the green emitting fluorophores the quinolinium part was replaced by a pyridinium group. The bridge to the indole group was attached either to the 2-position or to the 4-position of the pyridinium moiety. For the red-emitting dyes the connection to the indole moiety is at the 4-position of the quinolinium part. In each set of dyes a methyl group at the indole-NH and/or a phenyl group at the 2-position of the indole part were introduced to tune the optical properties and photostability. Additionally, two dyes were modified with a cyano group to tune the photophysical properties and to enhance the photostabilities. The developed dyes show good photostabilities and bright green or red fluorescence intensities in the presence of DNA. Thus, these dyes represent important and promising candidates for fluorescent molecular imaging of nucleic acids inside living cells.